2002
DOI: 10.1029/2001gl014325
|View full text |Cite
|
Sign up to set email alerts
|

Electrical structure across the Indus Tsangpo suture and Shyok suture zones in NW Himalaya using magnetotelluric studies

Abstract: [1] Magnetotelluric studies in the NW Himalayan region have shown anomalously high conductance of about 20,000 siemens in the crust beneath the Indus Tsangpo suture (ITS) and the adjoining Tso-Morari dome in the depth range of 1 -20 km. High heat flow and high attenuation of the seismic waves in the Himalayan crust, together with the observed high conductance indicate presence of wide spread partial melt generated from the subducted Indian crust. The Ladakh batholith appears as a resistive block to the north o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 9 publications
2
10
1
Order By: Relevance
“…The ratio is high for DDI station (> 0.30) located in the Northwest Himalaya. The medium-to-high value in the Northwest Himalaya region are consistent with a mafic/ ultramafic lower crust as inferred from other geophysical surveys (Gokarn et al 2002;Arora et al 2007). …”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…The ratio is high for DDI station (> 0.30) located in the Northwest Himalaya. The medium-to-high value in the Northwest Himalaya region are consistent with a mafic/ ultramafic lower crust as inferred from other geophysical surveys (Gokarn et al 2002;Arora et al 2007). …”
Section: Discussionsupporting
confidence: 68%
“…They have found out that the Moho depth reached up to 75 km on LadakhÀKarakoram and the thickness of Moho decreased southward to 40 km near the Indo-Gangetic basin. Caldwell et al (2009) reported a mid-crustal channelized liquid flow or a lowvelocity layer (LVL) from the southern Tibet detachment to the Northwest Himalaya region, in agreement with the previous magnetotelluric (MT) study by Gokarn et al (2002) and Arora et al (2007). The MT study by Arora et al (2007) inferred the presence of a low-resistivity (5À10V) layer in the middle crust from the southern detachment to Karakoram fault (KF).…”
Section: Introductionsupporting
confidence: 76%
See 2 more Smart Citations
“…The North West Himalaya in India has been studied as part of the HIMPROBE project that included teleseismic receiver function studies (Rai et al 2006) and MT surveys (Gokarn et al 2002a;Arora et al 2007). As in the Central Himalaya, the MT data image a dipping conductor located at the top of the underthrusting Indian Plate (Arora et al 2007).…”
Section: North West Indian Himalayamentioning
confidence: 99%